Fountain code based packets transmission over IP networks - Xu, Jian. (2013)
Fountain code is a new kind of channel code, which is error-tolerant and no feedback needed during transmission in network. LT codes and Raptor codes are two typical fountain codes for practical applications. In this paper, LT code is mainly discussed from perspective of degree distribution, encoding scheme, decoding scheme and also application model over IP networks.